Analysis of the Impact of Income and Total Assets on Net Profit in the Banking Industry From 2014 to 2023 (Case Study of Banking Companies Listed in IDX30) - Muhammad Haston Samudra Wicaksono (CV. Publikasi Indonesia, 2026)
Banking companies play a strategic role in supporting national economic growth, making their financial performance a primary concern for investors and stakeholders. Net profit is a crucial indicator for assessing a company’s performance and sustainability, and it is theoretically influenced by revenue and total assets. Discrepancies in previous research findings regarding the influence of revenue and total assets on net profit indicate the need for further empirical studies, particularly in the banking industry, which is characterized by high liquidity and substantial market capitalization. This study aims to analyze the effect of revenue and total assets on net profit in banking companies indexed in IDX30 for the period 2014–2023. The research employs a quantitative method using secondary data in the form of annual financial reports from PT Bank Central Asia Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, and PT Bank Negara Indonesia (Persero) Tbk. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests and supplemented by the coefficient of determination (R²) test, F-test, and t-test. Data processing was performed using the Statistical Package for the Social Sciences (SPSS) application. The results indicate that revenue has a positive and significant effect on net profit. Furthermore, total assets also have a positive and significant effect on net profit. These findings suggest that increased revenue and optimal management of total assets—both current and fixed assets—play a substantial role in enhancing net profit in banking companies listed in the IDX30 index.